A Low-Energy Adaptive Clustering Hierarchy Architecture with an Intersection-Based Coverage Algorithm in Wireless Sensor Networks - Young-Long Chen; Fu-Kai Cheung; Yung-Chi Chang (2013 Seventh International Conference on Innovative Mobile and Internet Services in Ubiquitous Computing, 2013)
In wireless sensor networks (WSNs), the sensor nodes are randomly deployed, and energy is limited. Energy consumption reduction is therefore very important. To extend the system lifetime, we used the intersection-based coverage algorithm (IBCA) to address lifetime, its introduction causes sensor nodes to enter sleep mode when not operating. This algorithm can achieve reduced energy consumption in transmission. And we then combine IBCA with Low-energy adaptive clustering hierarchy (LEACH) architecture to improve system performance. Simulation results show that the performance of our proposed LEACH architecture with IBCA perform better than LEACH architecture with phase-based coverage algorithm (PBCA) in terms of energy consumption, number of surviving nodes and sensing areas.